Potensi Bakteri Zoogloea Sp sebagai Bakteri Pembentuk Bioflok pada Sistem Pertambakan - Muhammad, Junda (Fakultas MIPA UNM, 2011)
The objective of this study was to know the potency of bacteria zoogloea sp as indigenous bacteria from shrimp pond farming in colonizing particles. Study of particle-colonizing capacity of Zoogloea sp by using artificial-sphare agar and transparant exopolimeric particles (TEP) produced by fitoplankton, Thalassiosira weisfloggii. The results showed that Zoogloea sp were able to coloninize both artificial-agar spheres and TEP produced by T. weisfloggii.The mean number of Zoogloea sp colonizing artificial-agar sphares increasing with incubation time was 2,70 x 104 cells/agar sphere. In the test of TEP-colonizing bacteria showed that Zoogloea sp was able to colonize the TEP i.e. 2.5 x 108 cells/mL. after 4 days incubation. It can be concluded that Zoogloea sp isolated from shrimp pond farming has a high potential in colonizing particles.